(untitled) (Journal of Solar Energy Research Updates, 2019)
Solar flat plate collectors (FPC) are used for heating spaces, water heating, and many other purposes. The present technology of solar flat collectors uses vertical fins. The solar flat plate collector having absorber with vertical fins is provided with a helical tape in the fluid flow path. The absorber plate in the solar flat plate collector has an area of 100 cm x 50 cm. The solar flat plate collector has nine ducts with an area of 27.5 cm x 9.5 cm each. The helical tapes attached have a start angle of 64 deg which pass along the whole length of the duct. The helical tapes have a crosssection area of 1.5 mm x 4 mm. The pitch of the helical tapes is 100 mm. These fins have been attached between the vertical fins of the thickness of 1mm and a height of 10.5 cm. Data such as inlet temperature, outlet temperature efficiency and convective heat transfer coefficient are calculated. The mass flow rate of air is 10.28 kg/s and the air is subjected to solar radiation between 628.98 W/m2 and 708.59 W/m2. The values are noted down, and the and the efficiency is noted to have a 10% rise. The effectiveness of the solar plate collector will increase using a helical fin. A comparative analysis will be done between the conventional flat plate collector and the setup with the helical tapes. The study will show that the helical tapes in flat plate collector will be the best alternative compared to conventional flat plate collector.